Climate change and its differential impact on sexual and reproductive health and rights among women in Nepal - Jagadishwor Ghimire; Jagadishwor Ghimire; Khusbu Poudel; Kritee Lamichhane; Amit Timilsina; Madhav Prasad Dhakal; Parash Prasad Phuyal; Sumanjari Pradhan; Jivan Devkota; Sujan Karki; Sujan Karki (Frontiers in Reproductive Health)
BackgroundNepal is highly affected by climate change, experiencing glacier melting, untimely rainfall, floods, landslides, forest fires, and droughts, which collectively impact over 10 million people. There is a larger impact of climate change on human health, but its impact on women's and girls’ sexual and reproductive health and rights is yet to be explored. Thus, this study aims to understand the linkages between climate change and the unique impact on gender and sexual, and reproductive health and rights (SRHR).MethodologyThis is an exploratory cross-sectional study conducted using a mixed method in Kailali, Arghakhanchi, and Kapilvastu districts. A total of 384 women were selected using systematic random sampling from the upper, middle, and downstream of Khutiya and Banganga river basins. Focus group discussions and key informant interviews were conducted to capture their experiences. Descriptive, bivariate, and multivariate analyses were carried out for quantitative data using SPSS, and a thematic analysis for qualitative data.ResultsThe women who experienced two or more climate-included disasters were more likely to face gender-based violence (P < .05). The study also showed that women's autonomy in making decisions on Sexual and Reproductive Health and Rights has increased among women exposed to a higher number of climate-related risk (P < .001). Though more than 3/4th of women did not want more children, women who are exposed to more climate-related risks wanted more children (P < .001). The survey found that more than three-quarters (76.3%) of respondents knew about the legality of abortion, and 85% of respondents knew the place to go for abortion services. The result also revealed a significant reduction in sexual desire among women who were exposed to a higher number of climate events. These findings are also aligned with the qualitative information in the study.ConclusionThe findings demand strengthening the resilience of healthcare systems to withstand the impact of climate change, ensuring that essential sexual and reproductive health services, including abortion, contraception, and maternal healthcare, are available and accessible even during the climate crisis. The findings indicate the need for interventions that empower women, address gender-based violence, and integrate sexual and reproductive health into climate change adaptation in policies and programs.